Euphrates-Tigris contact zone - Kosyan, Aram (ARAMAZD: Armenian Journal of Near Eastern Studies, 2017)
The civilizational role of contact zones has been a subject of several fundamental studies in the past. Contact zone is a territory located between two or more political, economic and cultural regions experiencing constant interaction on different levels where due to their ‘clash’ new civilizational units are coming into existence. The societies in contact zones are characterised by criteria of two or more civilizations which eventually lead to the formation of the so-called ‘daughter-civilizations’. Such permanent contacts are triggering the formation of a cultural environment, which consequently extends towards the ‘barbarian periphery’, a civilizational factor, which may be traced actually in a great number of regions of the Old and New worlds.